Artesunate activates mitochondrial apoptosis in breast cancer cells via iron-catalyzed lysosomal reactive oxygen species production - Hamacher-Brady, Anne; Stein, Henning Alexander; Turschner, Simon; Toegel, Ina; Mora, Rodrigo; Jennewein, Nina; Efferth, Thomas; Eils, Roland; Brady, Nathan R. (The journal of biological chemistry, 2011)
The antimalarial agent artesunate (ART) activates programmed cell death (PCD) in cancer cells in a manner dependent on the presence of iron and the generation of reactive oxygen species. In malaria parasites, ART cytotoxicity originates from interactions with heme-derived iron within the food vacuole. The analogous digestive compartment of mammalian cells, the lysosome, similarly contains high levels of redox-active iron and in response to specific stimuli can initiate mitochondrial apoptosis. We thus investigated the role of lysosomes in ART-induced PCD and determined that in MCF-7 breast cancer cells ART activates lysosome-dependent mitochondrial outer membrane permeabilization. ART impacted endolysosomal and autophagosomal compartments, inhibiting autophagosome turnover and causing perinuclear clustering of autophagosomes, early and late endosomes, and lysosomes. Lysosomal iron chelation blocked all measured parameters of ART-induced PCD, whereas lysosomal iron loading enhanced death, thus identifying lysosomal iron as the lethal source of reactive oxygen species upstream of mitochondrial outer membrane permeabilization. Moreover, lysosomal inhibitors chloroquine and bafilomycin A1 reduced ART-activated PCD, evidencing a requirement for lysosomal function during PCD signaling. ART killing did not involve activation of the BH3-only protein, Bid, yet ART enhanced TNF-mediated Bid cleavage. We additionally demonstrated the lysosomal PCD pathway in T47D and MDA-MB-231 breast cancer cells. Importantly, non-tumorigenic MCF-10A cells resisted ART-induced PCD. Together, our data suggest that ART triggers PCD via engagement of distinct, interconnected PCD pathways, with hierarchical signaling from lysosomes to mitochondria, suggesting a potential clinical use of ART for targeting lysosomes in cancer treatment.